2003
DOI: 10.1002/mds.10632
|View full text |Cite
|
Sign up to set email alerts
|

Psychogenic palatal tremor

Abstract: Recent criteria for the classification of palatal tremor use clinical, imaging, and electrophysiological features to differentiate essential and symptomatic forms. A case of probable psychogenic palatal tremor (PPT) is described within the context of these criteria, which lack clear guidelines for diagnosing PPT. The heterogenous nature of essential palatal tremor and its relationship with PPT, voluntary palatal movements, and tics is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…A) at rest: tremor bursts involve the genioglossal (traces 1,3,5,7) but not the digastric muscle (traces 2,4,6,8); B) active jaw opening: during the task sustained voluntary tonic activation of the digastric muscle is associated with tremor bursts stop in the genioglossal muscle (black arrows), which reappear after jaw closure (dotted arrows); C) passive jaw opening: between two brief voluntary phasic muscle contractions of the digastric muscle (arrows), necessary to allow insertion and removal of a small object to bite, muscle relaxation replaces tremor bursts in the genioglossal muscle. In each panel time base is 200 ms/div (each horizontal trace 4s); sensitivity 500 µV/div It has been reported that EPT can be modified by different manoeuvres including mental processing [2,11,15,22,25], neck position [23], speaking [4,11], singing [4] or mouth opening [2,25]. The findings observed in our patients confirm that mouth opening and other situations that imply mouth opening may completely suppress PT.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A) at rest: tremor bursts involve the genioglossal (traces 1,3,5,7) but not the digastric muscle (traces 2,4,6,8); B) active jaw opening: during the task sustained voluntary tonic activation of the digastric muscle is associated with tremor bursts stop in the genioglossal muscle (black arrows), which reappear after jaw closure (dotted arrows); C) passive jaw opening: between two brief voluntary phasic muscle contractions of the digastric muscle (arrows), necessary to allow insertion and removal of a small object to bite, muscle relaxation replaces tremor bursts in the genioglossal muscle. In each panel time base is 200 ms/div (each horizontal trace 4s); sensitivity 500 µV/div It has been reported that EPT can be modified by different manoeuvres including mental processing [2,11,15,22,25], neck position [23], speaking [4,11], singing [4] or mouth opening [2,25]. The findings observed in our patients confirm that mouth opening and other situations that imply mouth opening may completely suppress PT.…”
Section: Discussionsupporting
confidence: 92%
“…The disappearance of PT with mouth opening has been recently reported in some cases that have been interpreted as probable psychogenic palatal tremor [16,25].Williams [25] described a woman with a history of a generalised anxiety disorder who developed PT.That patient had intermittent and varying amplitude soft palate movements with ear clicks while she was at rest with her mouth closed. Muscle jerks disappeared with mouth opening, during which time several beats of palatal elevation could be voluntarily performed on request.Palatal tremor disappeared when the patient performed complex finger movements.The author concluded that the inconsistent character of movements, their increase with attention, their disappearance with distraction and the patient's history of psychopathological disorders were suggestive of a psychogenic aetiology.…”
Section: Discussionmentioning
confidence: 95%
“…2 Although tremor is a frequent psychogenic movement disorder manifestation, palatal tremor rarely has a psychogenic etiology. 1,3,4 Recently, Williams described a patient with probable psychogenic palatal tremor. 3 This patient presented with audible ear clicking, which was evaluated by tympanography.…”
mentioning
confidence: 98%
“…1,3,4 Recently, Williams described a patient with probable psychogenic palatal tremor. 3 This patient presented with audible ear clicking, which was evaluated by tympanography. The "mode of onset, intermittent nature, disappearance with mouth opening and voluntary control" of the patient's symptoms raised the question of a psychogenic etiology.…”
mentioning
confidence: 98%
See 1 more Smart Citation